Pandangan Kiai Pesantren terhadap Fenomena Long Distance Realationship (LDR) Pasangan Suami Istri di Kabupaten Jember: Kiai Pesantren's Views on the Long Distance Realation (LDR) Phenomenon of Married Couples in Jember Regency - Awaliya Safithri; Fajar Ainol Yakin; Hasbi Ash Shiddiqi (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The basic concept of marriage in Islam is the formation of a family that is Sakinah mawadah Warahmah. However, due to a situation that requires husband and wife to be separated by distance, they are in a long-distance relationship (LDR). In a household, husband and wife have rights and obligations that have become normative law (legal norms) that need to be considered by all parties in the household, both husband and wife. This type of research is field research, namely research conducted directly into the field to obtain complete and valid data. Data collection techniques are interviews and documentation. This interview was conducted to obtain information by interviewing informants, interviews were conducted with pesantren kiai in Jember district. The research method used is a qualitative research method. Data collection in this study was carried out using interviews and documentation techniques. While the analysis technique used is descriptive qualitative analysis. The results of this study indicate that the factor that causes the Long Distance Relationship (LDR) phenomenon for married couples in Jember Regency is the factor of career demands, there are some migrants from outside Jember Regency who have the status of a wife leaving her husband to carry out their duties as servants of the state (PNS). , and vice versa. There is a difference of opinion among Islamic boarding school kiai, the first group argues that LDR is not permitted for a wife, meaning that a wife must always be by her husband's side because a wife cannot possibly carry out her obligations to serve her husband in the household at a distance. And this has deviated from maqasid marriage, namely the creation of harmony in the household. the second group allows LDR if in an emergency. For example, the goal of a wife or husband is to be away from their partner for the demands of family maintenance, the argument for this group is the rule of ushul fiqh addhorurot bodiul mahdzurat.